Intima-media thickness cut-off values depicting “halo sign” and potential confounder analysis for the best diagnosis of large vessel giant cell arteritis by ultrasonography - Milchert, Marcin; Fliciński, Jacek; Brzosko, Marek (Frontiers in Medicine, 2022)
Background: Vascular ultrasound enables fast-track diagnosis of giant cell arteritis (GCA), but this method remains subjective. We aimed to determine intima-media thickness (IMT) cut-off values for large vessel GCA (LV-GCA) and identify the clinically relevant factors influencing it. Methods: We included 214 patients referred for ultrasound evaluation within fast-track clinic because of suspected GCA. IMT was measured in axillary, brachial, subclavian, superficial femoral and common carotid arteries (CCA), in a place without identifiable arteriosclerotic plaques. IMT cut-off values for vasculitis were determined by comparing measurements in arteries classified as vasculitis versus controls without GCA/PMR. Results: GCA was diagnosed in 81 individuals, including extracranial LV-GCA in 43. Isolated PMR was diagnosed in 50 subjects. In 83 remaining patients other diagnosis was confirmed and they served as controls. The optimal IMT cut-off values for the diagnosis of axillary vasculitis was 0.8 mm, subclavian - 0.7, superficial femoral - 0.9, CCA - 0.7, brachial - 0.5. The IMT cut-off values providing 100% specificity for vasculitis (although with reduced sensitivity) was reached with axillary IMT 1.06 mm, subclavian - 1.35 mm, superficial femoral - 1.55 mm, CCA - 1.27 mm, brachial - 0.96 mm. Axillary and subclavian arteritis provided the best AUC for the diagnosis of GCA (Table 5), while carotid and axillary were most commonly involved (24 and 23 patients respectively, Table 4). Presence of calcified atherosclerotic plaques were related to increase of IMT in both patients and controls while male sex, age ≥ 68, hypertension and smoking increased IMT in controls but not in GCA patients. Conclusion: Cut-off values for LV-GCA performed best in axillary and subclavian arteritis but expanding examination to the other arteries may add to the sensitivity of GCA diagnosis (another location e.g. brachial arteritis), and its specificity (identification of calcified atherosclerotic plaques in other arteries like CCA may suggest applying higher IMT cut-offs). We propose more linear approach to cut-off values with 2 values: one for most accurate and the other for highly specific diagnosis, and also considering some cardiovascular risk factors.